Contamination of chickens by Salmonella spp., in Brazil: an important public health problem - Andrade Júnior, Francisco Patricio de; Lima, Brenda Tamires de Medeiros; Lima, Brencarla de Medeiros; Cordeiro, Laísa Vilar; Barbosa, Vanessa Santos de Arruda; Lima, Edeltrudes de Oliveira (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Introduction: Bacteria of the genus Salmonella are important pathogens involved in the contamination of various foods, such as chickens, and may cause food poisoning. Aim: The present study aimed to review the literature on the prevalence of chickens contaminated with Salmonella spp., which are commercializated in different Brazilian states. Material and methods: This was a literary review. The absolute frequency and the total percentage of contaminated samples was calculated and the Qui-square statistical test was applied, considering statistically significant p <0.05. Results: 616 publications were retrieved, but only 10 articles were included to compose the results. The cataloged studies were carried out in 14 different brazilian states, and it was observed that of 5,030 chicken samples analyzed, the mean prevalence of samples contaminated with Salmonellawas 7,3% (n= 365). In addition, the prevalence of samples in the different studies ranged from 2.5% to 44.6%. The most prevalent serotype was S. Enteritidis (28,7%) and a statistically significant association between the type of raw material for commercialization and the result of the chicken samples microbiological analysis was observed (p<0.001), where the carcasses represented 90.1% of the contaminated samples. Conclusion: Thus, the data presented in this study can serve as subsidy for the development of necessary, political or legislative, measures that allow a better control of commercialized chickens in Brazil. Descriptors: Salmonella; Foodborne Diseases; Epidemiology. References Souza GC, Gonsalves HRO, Gonsalves HEO, Coêlho JLS. Característica microbiológica da carne de frango. ACSA. 2014;10(1):12-17. Pinto LAM, Pinto MM, Bovo J, Mateus GAP, Tavres FO, Baptista ATA, et al. Aspectos ambientais do abate de aves: uma revisão. Rev Uningá. 2018;22(3):44-50. Oliveira ME, Oliveira RLZ, Souza MFLZ, Harada ES, Tech ARB. Desenvolvimento de sensores para monitoramento de ambiente aviário com ênfase em controle térmico. Int J Agric & Biol Eng. 2018;12(3):234-40. Cintra APR, Andrade MCG, Lazarini MM, Assis DCS, Silva GR, Menezes LDM, et al. Influence of cutting room temperature on the microbiological quality of chicken breast meat. Arq Bras Med Vet Zootc. 2016;68(3):814-20. Rückert DAS, Pinto PSA, Santos BM, Moreira MAS, Rodrigues ACA. Pontos críticos de controle de Salmonella spp. no abate de frangos. Arq Bras Med Vet Zootec. 2009;61(2):326-30. Oliveira AP, Sola MC, Feistel JC, Moreira NM, Oliveira JJ. 2013. Salmonella enterica: genes de virulência e ilhas de patogenicidade. Enciclopedia Biosfera. 2013;9(16):1947-72. Brasil. Ministério da Saúde [homepage na internet]. Surtos de doenças transmitidas por alimentos no Brasil [acesso em 15 jul 2018]. Disponível em: http://portalarquivos2.saude.gov.br/images/pdf/2018/julho/02/Apresentacao-Surtos-DTA-Junho-2018.pdf. Borsoi A, Moraes HLS, Salle CTP, Nascimento VP. Número mais provável de Salmonella isoladas de carcaças de frango resfriadas. Ciênc Rural. 2010;40(11):2338-42. Cardoso KF, Rall VLM, Mendes AA, Paz ICLA, Komiyama CM. Pesquisa de salmonella e coliformes termotolerantes em cortes de frango obtidos no comércio de Botucatu/SP. Hig Aliment. 2009;23(176/179):165-68. Cunha-Neto AD, Carvalho LA, Carvalho RCT, Dos Prazeres Rodrigues D, Mano SB, Figueiredo EES, Conte-Junior CA. Salmonella isolated from chicken carcasses from a slaughterhouse in the state of Mato Grosso, Brazil: antibiotic resistance profile, serotyping, and characterization by repetitive sequence-based PCR system. Poult Sci. 2018;97(4):1373-81. Duarte DAM, Ribeiro AR, Vasconcelos AMM, Santos SB, Silva JVD, Andrade PLA, et al. Occurrence of Salmonella spp. in broiler chicken carcasses and their susceptibility to antimicrobial agents. Braz J Microbiol. 2009;40(3):569-73. Medeiros MA, Oliveira DC, Rodrigues DP, Freitas DR. Prevalence and antimicrobial resistance of Salmonella in chicken carcasses at retail in 15 Brazilian cities. Rev Panam Salud Publica. 2011;30(6):555-60. Menezes LDM, Lima AL, Pena EC, Silva GR, Klein RWT, Silva CA, et al. Caracterização microbiológica de carcaças de frangos de corte produzidas no estado de Minas Gerais. Arq Bras Med Vet Zootec. 2018;70(2):623-27. Moreira GN, Rezende CSM, Carvalho RN, Mesquita SQP, Oliveira AN, Arruda MLT. Ocorrência de Salmonella sp. em carcaças de frangos abatidose comercializados em municípios do estado de Goiás. Rev Inst Adolfo Lutz. 2008;67(2):126-30. Possebon FS, Costa LFZP, Yamatogi RS, Rodrigues MV, Sudano MJ, Pinto JPAN. A refrigeração no diagnóstico de Salmonella spp. utilizando o método microbiológico tradicional e reação em cadeia da polimerase em carcaças de frango. Ciênc Rural. 2012;42(1):131-35. Tessari ENC, Cardoso ALSP, Kanashiro AMI, Stoppa GFZ, Luciano RL, Castro AGM. Ocorrência de Salmonella spp. em carcaças de frangos industrialmente processadas procedentes de explorações industriais do Estado de São Paulo, Brasil. Cienc Rural, 2008; 38(9):2557-60. Yamatogi RS, Galvão JA, Baldini ED, Souza Júnior LCT, Rodrigues MV, Pinto JPAN. Avaliação da unidade analítica na detecção de Salmonella spp. em frangos a varejo. Rev Inst Adolfo Lutz. 2011;70(4):637-40. Sharma J, Kumar D, Hussain S, Pathak A, Shukla M, Kumar VP, et al. Prevalence, antimicrobial resistence and virulence genes characterization of montyphoidal Salmonella isolated from retail chicken meat shops in Northern India. Food Control. 2019;102:104-11. Harb A, Babib I, Mezal EH, Kareem HS, Laird T, O’dea M, et al. Ocurrence, antimicrobial resistence and whole-genome sequencing analysis of Salmonella isolates from chicken carcasses imported into Iraq from four different countries. Int J Food Microbiol. 2018;284:84-90. Zwe YH, Yentang VC, Aung KT, Gutiérrez RA, Ng LC, Yuk HG. Prevalence, sequence types, antibiotic resistance and, gyrA mutations of Salmonella isolated from retail fresh chicken meat in Singapore. Food Control. 2018;90:233-40. Goni AM, Effarizah ME, Rusul G. Prevalence, antimicrobial resistance, resistance genes and class 1 integrons of Salmonella serovars in leafy vegetables, chicken carcasses and related processing environments in Malaysian fresh food markets. Food Control. 2018;91:170-80. Zhu J, Wang Y, Song X, Cui S, Xu H, Yang B, et al. Prevalence and quantification of Salmonella contamination in raw chicken carcasses at the retail in China. Food Control. 2014;44:198-202. Kramarenko T, Nurmoja I, Karssin A, Meremae K., Horman A, Roasto M. The prevalence and serovar diversity of Salmonella in various food products in Estonia. Food Control. 2014;42:43-7. Smadi H, Sargeant JM, Shannon HS, Raina P. Growth and inactivation of Salmonella at low refrigerated storage temperatures and thermal inactivation on raw chicken meat and laboratory media: Mixed effect meta-analysis. Journal of Epidemiology and global Health. 2012;2(4):165-79. Cardoso ALSP, Tessari ENC. Salmonella enteritidis em aves e na saúde pública: revisão da literatura. R cient eletr Med Vet. 2013;11(21). Realpe-Delgado ME, Muñoz-Delgado AB, Donado-Godoy P, Rey-Ramírez LM, Díaz-Guevara PL, Arévalo-Mayorga SA. Epidemiología de Salmonella spp., Listeria monocytogenes y Campylobacter spp., en la cadena productiva avícula. Iatreia. 2016;22(4):397-406. Shinohara NKS, Barros VB, Jimenez SMC, Machado ECL, Dutra RAF, Lima Filho JL. Salmonella spp., importante agente patogênico veiculado em alimentos. Ciênc. sáude coletiva. 2008;13(5):1675-83. Lv S, Si W, Yu S, Li Z, Wang X, Chen L, Zhang W, Liu S. Characteristics of invasion-reduced hilA gene mutant of Salmonella Enteritidis in vitro and in vivo. Res Vet Sci. 2015;101:63-8. Feasey NA, Hadfield J, Keddy KH, Dallman TJ, Jacobs J, Deng X, et al. Distinct Salmonella Enteritidis lineages associated with enterocolitis in high-income settings and invasive disease in low-income settings. Nat Genet. 2014;48(10):1211-17.